2014
DOI: 10.1007/s11255-014-0759-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term durability, functional outcomes, and factors associated with surgical failure of tension-free vaginal tape procedure

Abstract: TVT is an effective long-term treatment for SUI, although the cure rate may decrease with time. A low VLPP was predictive of SUI recurrence, and patients showing no OAB symptoms tended to be younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…In Serati's series, the percentage of women with de novo urgency was also slightly higher (18.9% at 10 years), although women in these series were substantially younger and women with mixed UI were excluded . In Han's series with a follow‐up of 12 years, a de novo urgency and urge UI developed in 40.5% and 17.2% of the patients, respectively . Svenningsen et al reported on a 10 years de novo urge incontinence rate of 14.9% .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In Serati's series, the percentage of women with de novo urgency was also slightly higher (18.9% at 10 years), although women in these series were substantially younger and women with mixed UI were excluded . In Han's series with a follow‐up of 12 years, a de novo urgency and urge UI developed in 40.5% and 17.2% of the patients, respectively . Svenningsen et al reported on a 10 years de novo urge incontinence rate of 14.9% .…”
Section: Discussionmentioning
confidence: 91%
“…Han et al reported on 88 patients who were followed for at least 12 years (a potential bias of this cohort is that only women who were cured after 6 months were followed long‐term). The cure rate at 12 years was 79.6% . Svenningsen et al reported on the 10 years outcome of 483 patients treated in four Norwegian centres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the non-RCT studies, SUI was clinically diagnosed in eight (no urodynamic studies performed) [26,34,36,41,48,51,53,60] and a blinded assessment was performed in only three [40,50,51] (Figure in Electronic supplementary material). Outcome was assessed as a composite measure of cure (objective and subjective definition of cure met) [20,24,30,31,35,59], subjective [14,19,21,26,34,36,38,39,42,44,48], objective outcome [15,16,22,50] or both [17, 18, 23, 25, 27-29, 32, 33, 37, 40, 41, 43, 45-47, 49, 51-58, 60-62]. The follow-up was described in each study with a minimum of 36 months and a maximum of 17 years.…”
Section: Resultsmentioning
confidence: 99%